Taking the Bitter with the Sweet: Sugar Refiners and the Canadian Regulatory State, 1904-20 - Cruikshank, Ken (Canadian Historical Review, 1993)
Keywords: Sucre

La région de Montréal face au déclin des dépenses militaires - Bélanger, Yves (Cahiers de géographie du Québec, 1993)
Keywords: Armée

Georges Vanier - Bertrand, Luc (Célébrités canadiennes, 1993)
Les diverses étapes de la prestigieuse carrière de cet ancien gouverneur général du Canada.

L'intégration des forces policières sur le territoire de la communauté urbaine de Montréal, genèse et évaluation - Bissonnette, Sylvain (Université de Montréal, 1993)
Keywords: Communauté urbaine; Police

Property and Marriage: the Law and the Practice in Early Nineteenth-Century Montreal - Bradbury, Bettina; Stewart, Alan; Kolish, Evelyn; Gossage, Peter (Histoire sociale / Social History, 1993)
Keywords: Droit; Mariage

La consultation publique à Montréal: un affaire de femmes? - Cloutier, Céline (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Hormidas [Hormisdas] Laporte (1850-1934). Une petite maison, un grand homme - Cloutier, Gabrielle (Cahiers d'histoire du Sault-au-Récollet, 1993)
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

Les stratégies fiscales municipales et les enjeux de la décentralisation des services publics: le cas de Montréal - Collin, Jean-Pierre (Les stratégies fiscales municipales et les enjeux de la décentralisation des services publics: le cas de Montréal, 1993)
Keywords: Fiscalité

Dynamiques d'une bureaucratie: l'administration municipale de Montréal et ses fonctionnaires: 1900-1945 - Dagenais, Michèle (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1993)
Keywords: Fonctionnaires; Hôtel de ville; Réformistes

Le chevalier oublié - de Lagrave, Jean-Paul (Cap-aux-Diamants, 1993)
Keywords: Chomedey de Maisonneuve, Paul de (Maisonneuve, Paul de Chomedey de)

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

«C'est l'eau-de-vie qui a commis ce meurtre». Alcool et criminalité amérindienne à Montréal sous le Régime français - Dickinson, John A. (Études canadiennes / Canadian Studies, 1993)
Keywords: Alcool; Autochtones; Criminalité

La Nouvelle-France sous Joseph-Antoine Le Febvre de La Barre, 1682-1685: lettres, mémoires, instructions et ordonnances - Dubé, Pauline (Septentrion, 1993)
Keywords: Autochtones; Français; Gouverneurs

La prison de Montréal de 1865 à 1913: évolution en longue période d'une population pénale - Fecteau, Jean-Marie; Tremblay, Marie-Josée; Trépanier, Jean (Les Cahiers de Droit, 1993)
Keywords: Prisons

Le rôle des municipalités québécoises en matière de gestion des terrains contaminés: le cas de Montréal - Fontaine, Josée (Université de Montréal, 1993)
Keywords: Pollution

Étude lexicale du livre des recettes et dépenses de l'Hôtel-Dieu de Montréal (1696 à 1726) - Francoeur, Sylvie (Université de Montréal, 1993)
Keywords: Communautés religieuses; Hospitalières de Saint-Joseph; Hôpitaux; Hôtel-Dieu; Linguistique

Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives - Fyson, Donald; M. Coates, Colin; Harvey, Kathryn (Occasional Papers of the Montreal History Group, 1993)
Keywords: Criminalité; Mariage; Police; Prostitution; Travail; Tribunaux

Entrevue avec Phyllis Lambert - Gagnon-Pratte, France (Continuité, 1993)
Keywords: Centre canadien d'architecture; Lambert, Phyllis

Les décisions pénales dans les causes d'homicide au tribunal de Montréal, de 1985 à 1989 - Grandmaison, Rachel (Université de Montréal, 1993)
Keywords: Criminalité; Tribunaux

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs

La fin d'un univers féminin: l'Enquête Caron et la prostitution, 1945-1965 - Lacasse, Danielle (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Prostitution

Wage Disputes and the Courts in Montreal, 1816-1835 - Laing Hogg, Grace; Shulman, Gwen (Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives, 1993)
Keywords: Travail; Tribunaux

L'apport des coalitions de quartier dans l'élargissement de la démocratie locale - Lambert, Claudette (Université du Québec à Montréal, 1993)
Keywords: Groupes populaires

La place de Médéric Lanctôt dans l'évolution du nationalisme québécois - Lefebvre, Luc (Université de Montréal, 1993)
Keywords: Lanctôt, Médéric; Nationalisme

Les limites de la démocratie, les frontières de l'autonomie - Lustiger-Thaler, Henri (Recherches sociographiques, 1993)
Keywords: Groupes populaires; Hôtel de ville; Maires; Rassemblement des citoyens et citoyennes de Montréal

La ville: un milieu d'engagement politique privilégié pour les femmes: le cas de Montréal - Maillé, Chantal (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Histoire des maires de Montréal - Marsolais, Claude-V.; Desrochers, Luc; Comeau, Robert (Études québécoises, 1993)
Keywords: Maires

Les Québécoises et le mouvement pacifiste (1939-1967) - Monet-Chartrand, Simonne (Écosociété, 1993)
Keywords: Femmes; Guerre

Women Policing Women: A Patrol Woman in Montreal in the 1910s - Myers, Tamara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
Keywords: Femmes; Police

Les maires de Saint-Laurent et les conseils municipaux: une histoire à découvrir - Nadon, Mario (Ville de Saint-Laurent et Groupe Litho-Graphic, 1993)
Keywords: Conseillers municipaux; Maires; Saint-Laurent (ville)

Élaboration d'un modèle pour orienter la gestion d'un processus de regroupement des services municipaux de police en région urbaine - Ouellet, Michel (Université du Québec à Chicoutimi, 1993)
Keywords: Police

Les femmes et la prise de décision au niveau municipal - Pelletier, Lyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Conseillers municipaux; Femmes

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

Reflections of Montreal Prostitution in the Records of the Lower Courts, 1810-1842 - Poutanen, Mary-Anne (Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives, 1993)
Keywords: Criminalité; Police; Prostitution; Tribunaux

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger, Jacques

Les perceptions des groupes ethno-culturels face aux programmes communautaires du S.P.C.U.M. - Théagène, Jean-Manassé (Université de Montréal, 1993)
Keywords: Communauté urbaine

La pensée constitutionnelle du juge Pierre-Basile Mignault - Tremblay, Guy-Gérard (Les Cahiers de Droit, 1993)
Keywords: Juges